Analysis of Factors Affecting CO2 Emissions: In the Case of Uzbekistan - Saribayevich , Xolmurotov Fozil; Sariyevich, Xolmuratov Xolilla; Davlatov, Sukhrob; Turobova, Hulkar; Ruziyev, Sobirjon (International Journal of Energy Economics and Policy, 2024)
In this study, the influence of various factors on CO2 emissions in Uzbekistan during the period 1992-2020 was studied. The study examines the effect of forest area, urban population growth, renewable energy consumption, fossil fuel energy consumption, per capita energy consumption and industrial activity on observed CO2 emissions. Data were analyzed using multivariate linear regression, the D’Agostino skewness test, and the Anscombe-Glynn kurtosis tests. The results show that forest area has a significant negative correlation with CO2 emissions, suggesting that increased forest cover helps reduce emissions. Urban population growth shows a positive correlation with CO2 emissions, emphasizing the need for sustainable urbanization practices. Renewable energy consumption has been found to have a negative impact on emissions, promoting the adoption of clean energy sources. Fossil fuel energy consumption reveals a complex relationship, with different fuels contributing differently to emissions. Per capita energy consumption and industrial activity contribute significantly to emissions, requiring the adoption of energy-efficient technologies and sustainable industrial practices.